Exploring the genetic correlation and causal relationships between breast cancer and meningioma using bidirectional Mendelian randomization - Lu Ding; Bo Chen; Zhou Zhou; Zhaojun Mei; Kan Cao; Xinyu Lu; Wei Chen (Scientific Reports)
Abstract Previous studies have indicated a significantly higher prevalence of breast cancer (BC) among female patients with meningioma compared to the general female population. Therefore, this study aimed to assess the causal relationship between BC and meningioma at the genetic level. Genetic instrumental variables (IVs) for BC were identified from the Breast Cancer Association Consortium (BCAC), the Discovery Biology and Risk of Inherited Variants in Breast Cancer Consortium (DRIVE), the Collaborative Oncological Gene-environment Study (iCOGS), and 11 other BC genome-wide association studies (GWAS). Meningioma GWAS data were obtained from the FinnGen consortium and were further divided into intracranial and spinal meningioma groups for analysis. The primary analysis employed the inverse-variance weighted (IVW) method, supported by sensitivity analysis to address pleiotropy and enhance robustness. Next, linkage disequilibrium score regression (LDSC) was used to assess the genetic correlation between BC and meningioma. Finally, we applied the Functional Mapping and Annotation (FUMA) platform to conduct an in-depth analysis of the GWAS data. After rigorous screening and Mendelian randomization (MR) tests, genetically predicted overall BC (OR: 1.17, P = 0.0045) and ER(estrogen receptors) + BC (OR: 1.21, P = 0.0006) showed a potential causal association with intracranial meningioma. No causal relationships were found between intracranial meningioma and three BC subtypes. No bidirectional causal relationships were found between spinal meningioma and any BC subtype. The LDSC results suggested a modest positive genetic correlation between overall BC (rg: 0.152, SE: 0.077, P = 0.048), ER + BC (rg: 0.181, SE: 0.086, P = 0.035), and intracranial meningioma. FUMA analysis identified PITPNB, TTC28, and CHEK2 as shared risk genes between overall BC, ER + BC, and intracranial meningioma. These findings suggest that BC, especially ER + BC, may be a risk factor for intracranial meningioma. ER-related signaling pathways and the regulation of DNA damage may play a critical role in the pathogenesis of both diseases.